Konstruksi Wacana Religius dan Legitimasi Islamisasi Jawa dalam Kitab Aḥlā Al-Musāmarah Karya Syekh Abul Fadhol Senori: Analisis Wacana Kritis Van Dijk - Nawawi, Muhammad Imam; Baihaqi, M; Sholiha, Nur Lailatus; Abdurrahman, Muzakki; Syaifullah, Muhammad Dhiya' (Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2026)
This study examines the religious discourse in Aḥlā al-Musāmarah fī Ḥikāyati al-Awliyā’ al-‘Asyrah by Shaykh Abūl Faḍhol Senori using Teun A. van Dijk’s Critical Discourse Analysis (CDA) model. The main objective is to reveal how microstructure, superstructure, and macrostructure are employed in the text to convey social, political, and religious messages within the historical transition from the Majapahit Kingdom to the Islamic Sultanate of Demak. The research applies a qualitative-descriptive method with a critical discourse approach. The data consist of textual units analyzed across three dimensions: microstructure (semantics, syntax, stylistics, rhetoric), superstructure (narrative pattern), and macrostructure (global theme and supporting subthemes). The findings indicate that, at the micro level, the author employs detailed narration, lexical choices, and sentence constructions to reinforce moral and religious messages. At the superstructural level, the text is systematically organized into introduction, content, and conclusion, strengthening narrative coherence. At the macro level, the global theme highlights the collapse of Majapahit, the rise of Demak, and the pivotal role of the wali in the Islamization of Java. These results demonstrate that classical Nusantara texts not only preserve historical values but also serve as a medium of critical and transformative religious discourse. This research contributes to enriching critical discourse analysis in the field of Islamic studies in Indonesia and fosters academic dialogue between global theory and local texts.